Watching You : Joseph O$1 (BLoughlin #7 /s - Robotham, Michael, 1960- (New York : Mulholland Books, 2014)
"Before I Go to Sleep meets When a Stranger Calls in Robotham's taut and nuanced new thriller. Marnie Logan often feels like she's being watched: a warm breath on the back of her neck, or a shadow in the corner of her eye that vanishes when she turns her head. Now her life is frozen. Her husband Daniel is missing. She can't access his bank accounts or his life insurance. Depressed and increasingly desperate, she seeks the help of clinical psychologist Joe O'Loughlin. O'Loughlin discovers Daniel's Big Red Book--a collage of pictures, interviews, and anecdotes. The book, which Daniel intended as a surprise birthday gift, now leads to a shocking discovery. Any person who has ever crossed Marnie has paid an exacting price. And O'Loughlin may be next in line"--.
Keywords: Psychologists -- Fiction; Missing persons -- Fiction; FICTION / Psychological; FICTION / Thrillers; FICTION / Family Life; Suspense fiction; Psychological fiction